The Relationship Between Recruitment And Human Resources Professionalism In The Manufacturing Company Segment - Erialdy, Erialdy (Innovative: Journal Of Social Science Research, 2024)
To achieve professionalism in human resources that is reliable and in line with what the company needs, human resource management (HR) is something important, so there needs to be careful planning starting from recruitment. The aim of the research is to determine the relationship between recruitment and human resource professionalism in the manufacturing company segment. This research method is quantitative research with a sample of 48 people from a population of 170 employees. Data was collected using questionnaires, literature studies, observations and interviews testing instruments with validity and reliability tests. For data analysis using simple correlation analysis, multiple correlation analysis, coefficient of determination analysis, t statistical test, using the help of (SPSS) 25 for windows . Research results show that there is a positive and significant relationship between recruitment and human resource professionalism in companies in the Manufacturing Segment. This shows that recruitment and human resource professionalism in the Manufacturing company segment have a strong relationship.